Joint and tendon involvement predict disease progression in systemic sclerosis: a EUSTAR prospective study. Issue 1 (27th August 2014) - Avouac, Jérôme; Walker, Ulrich A; Hachulla, Eric; Riemekasten, Gabriela; Cuomo, Giovanna; Carreira, Patricia E; Caramaschi, Paola; Ananieva, Lidia P; Matucci-Cerinic, Marco; Czirjak, Laszlo; Denton, Christopher; Ladner, Ulf Müller; et al.
Abstract : Objective: To determine whether joint synovitis and tendon friction rubs (TFRs) can predict the progression of systemic sclerosis (SSc) over time. Patients and methods: We performed a prospective cohort study that included 1301 patients with SSc from the EUSTAR database with disease duration ≤3 years at inclusion and with a follow-up of at least 2 years. Presence or absence at clinical examination of synovitis and TFRs was extracted at baseline. Outcomes were skin, cardiovascular, renal and lung progression. Overall disease progression was defined according to the occurrence of at least one organ progression. Results: Joint synovitis (HR: 1.26, 95% CI 1.01 to 1.59) and TFRs (HR: 1.32, 95% CI 1.03 to 1.70) were independently predictive of overall disease progression, as were also the diffuse cutaneous subset (HR: 1.30, 95% CI 1.05 to 1.61) and positive antitopoisomerase-I antibodies (HR: 1.25, 95% CI 1.02 to 1.53). Regarding skin progression, joint synovitis (HR: 1.67, 95% CI 1.06 to 2.64) and TFRs (HR: 1.69, 95% CI 1.02 to 2.77) were also independently predictive of worsening of the modified Rodnan skin score. For cardiovascular progression, joint synovitis was predictive of the occurrence of new digital ulcer(s) (HR: 1.45, 95% CI 1.08 to 1.96) and decreased left ventricular ejection fraction (HR: 2.20, 95% CI 1.06 to 4.57); TFRs were confirmed to be an independent predictor of scleroderma renal crisis (HR: 2.33, 95% CI 1.03 to 6.19). Conclusions: Joint synovitis and TFRs are independent predictive factors for disease progression in patients with early SSc. These easily detected clinical markers may be useful for the risk stratification of patients with SSc.